Development of A PCR - Cycle Sequencing System for Animal Mitochondrial DNA Analysis - Lau, Chin Hoon (1994)
A system for the study of sequence polymorphisms in animal mitochondrial DNA was developed. This system consists of two candidate markers which are mitochondrial cytochrome b and D-loop. Six novel primers were constructed for their amplifications by polymerase chain reaction (PCR). The primers KY1 and KY2 amplified a 359-bp port ion of the cytochrome b gene from chicken, water buffalo, horse, goat and sheep. Primers UPM257 and UPM258 were used to synthesize a 1.4 Kb-fragment containing the complete chicken mi tochondrial D-loop. Primers LCH4-DO and LCH2-UP paired with primers UPM257 and UPM258 respectively to amplify a 355-bp 5' region and 395-bp 3' region of the D-loop. These primers were specific in their amplifications. The mitochondrial DNA could be amplified from heterogeneous or degraded DNA preparations, as well as directly from blood incubated in proteinase K thus bypassing lengthy DNA isolation steps.Only 5ul of blood was required for a l00-ul PCR. Fort he purification of PCR products, ethanol selective precipitation was found to be both efficient and economical. Despite its lower recovery compared to the Chroma Spin column, sufficient quantity of DNA could be obtained for subsequent sequencing.